2012
DOI: 10.1111/j.1365-2966.2012.20808.x
|View full text |Cite
|
Sign up to set email alerts
|

Shock fronts, electron-ion equilibration and intracluster medium transport processes in the merging cluster Abell 2146

Abstract: We present a new 400-ks Chandra X-ray observation of the merging galaxy cluster Abell 2146. This deep observation reveals detailed structure associated with the major merger event including the Mach number M = 2.3 ± 0.2 bow shock ahead of the dense, ram pressure stripped subcluster core and the first known example of an upstream shock in the intracluster medium (ICM) (M = 1.6 ± 0.1). By measuring the electron temperature profile behind each shock front, we determine the time-scale for the electron population t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
60
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 79 publications
6
60
0
Order By: Relevance
“…1 While Coulomb collisions will eventually drive electrons and protons to equal temperatures, the collisional equilibration timescale (Spitzer 1962) for typical conditions in the intracluster medium (ICM) is as long as 10 8 − 10 9 yrs. In fact, X-ray observations by Russell et al (2012) have shown that the electron temperature just behind a merger shock in Abell 2146 is lower than the mean gas temperature expected from the Rankine-Hugoniot jump conditions, and thus lower than the proton temperature. On the other hand, Markevitch (2006) found that the temperatures across the shock in 1E 0657-56 (the so-called "Bullet cluster") are consistent with instant shock-heating of the electrons.…”
Section: Introductionmentioning
confidence: 95%
“…1 While Coulomb collisions will eventually drive electrons and protons to equal temperatures, the collisional equilibration timescale (Spitzer 1962) for typical conditions in the intracluster medium (ICM) is as long as 10 8 − 10 9 yrs. In fact, X-ray observations by Russell et al (2012) have shown that the electron temperature just behind a merger shock in Abell 2146 is lower than the mean gas temperature expected from the Rankine-Hugoniot jump conditions, and thus lower than the proton temperature. On the other hand, Markevitch (2006) found that the temperatures across the shock in 1E 0657-56 (the so-called "Bullet cluster") are consistent with instant shock-heating of the electrons.…”
Section: Introductionmentioning
confidence: 95%
“…While Coulomb collisions will eventually drive electrons and protons to equal temperatures, the collisional equilibration timescale (Spitzer 1962) for typical ICM conditions is as long as 10 8 − 10 9 yrs. In fact, X-ray observations by Russell et al (2012) have shown that the electron temperature just behind a merger shock in Abell 2146 is lower than the mean gas temperature expected from the Rankine-Hugoniot jump conditions, and thus lower than the proton temperature. As a separate evidence, Akamatsu et al (2017) has compiled a list of merger shocks, estimating their Mach number from both X-ray (M s,X−ray ) and radio observations (M s,radio ), and noticed a slight bias of M s,radio M s,X−ray .…”
Section: Introductionmentioning
confidence: 95%
“…Fainter X-ray emission is found surrounding the subcluster core and this emission seems to be part of a second, larger subcluster that likely extends beyond the northern boundary of the Chandra image. There is no clear surface brightness peak corresponding to the primary cluster core, which suggests the primary cluster has been disrupted by the collision with the subcluster, as has been the case for A2146 (Russell et al 2012). The ICM temperature was fit using XSPEC with an absorbed singletemperature APEC model, which describes emission from collisionally-ionized diffuse plasma.…”
Section: Resultsmentioning
confidence: 92%